The unexplored potential of quinone methides in chemical biology - Di,Antonio M; Minard,A; Liano,D; Wang,X (Bioorganic and Medicinal Chemistry, 2019)
Quinone methides (QMs) are transient reactive species that can be efficiently generated from stable precursors under a variety of biocompatible conditions. Due to their electrophilic nature, QMs have been widely explored as cross-linking agents of DNA and proteins under physiological conditions. However, QMs also have a diene character and can irreversibly react via Diels-Alder reaction with electron-rich dienophiles. This particular reactivity has been recently exploited to label biomolecules with fluorophores in living cells.QMs are characterised by two unique properties that make them ideal candidates for chemical biology applications: i) they can be efficiently generated in situ from very stable precursors by means of bio-orthogonal protocols ii) they are reversible cross-linking agents, making them suitable for “catch and release” target-enrichment experiments. Nevertheless, there are only few examples reported to date that truly take advantage of QMs unique chemistry in the context of chemical-biology assay development. In this review, we will examine the most relevant examples that illustrate the benefit of using QMs for chemical biology purposes and we will anticipate novel approaches to further their applications in biologically relevant contexts.